Perkembangan Kemandirian Sosial Anak Usia Dini Dilihat Dari Status Ekonomi Orang Tua - Malikatus Sholihah; Nurul Afifah; Ulya Ainur Rofi’ah (Alzam: Journal of Islamic Early Childhood Education, 2022)
This study describes the development of early childhood social independence at RA Bustanul Wildan Karangrejo in the 2021/2022 academic year. The theories used as the basis for conducting this research include the theory of early childhood social independence and the theory of parents' economic status. The approach in this study uses a qualitative approach with descriptive analysis of the data that has been collected by interview and observation documentation methods. Triangulation of data by comparing data from different instruments and observers. Based on the results of the study, it can be concluded that the development of social self-esteem in early childhood at RA Bustanul Wildan in the 2021/2022 school year tends to be good. And there is no relationship between the development of children's social independence and the economic status of parents.